Pharmacy residency training measured through a standardized knowledge test. (15th December 2016) - Thompson, Amy N.; McKinzie, Brian P.; Haney, Jason S.; Nappi, Jean M.; Pilch, Nicole
Abstract: Purpose: The use of a standardized knowledge test to assess postgraduate year 1 (PGY1) pharmacy residency training was evaluated. Methods: This was a retrospective review of a prospectively administered exam. A bank of questions was developed by preceptors from each of the core rotation disciplines: general medicine (including ambulatory care and oncology), pediatrics, critical care (including transplantation), drug information, operations, practice management, and psychiatry. Board-certified pharmacy specialists at our institution were asked to submit 5–10 questions with answers that would likely be encountered by residents during rotation in their specific specialty area. The exam was administered at the beginning and the end of the resident's PGY1 year. Results: A total of 49 PGY1 residents completed the examination during the first and last months of their residency training. Residents' overall scores improved 5–10% annually from baseline to completion of their residency. The mean overall exam score significantly improved from baseline after completion of a PGY1 residency at our institution for all four class years. All four residency classes demonstrated an increase from baseline scores in most core disciplines with the exception of practice management, which decreased every year of the examination. Conclusion: Scores on a standardized exam developed to assess the baseline knowledge of incoming PGY1 residents and the effect of one year of residency training improved in the majority of practice areas at the end of the year compared to scores at the beginning of the year.